Unfinished Christians: ritual objects and silent subjects in late antiquity - Frank, Georgia (University of Pennsylvania Press, 2023)
"This book explores the sensory and affective dimensions of ordinary Christians' ritual lives in late antiquity. With few first-person accounts by ordinary Christians, it relies on written sources not typically associated with lived religion: sermons, liturgical instruction books, and festal hymns from Greek-speaking communities during the fourth through sixth centuries"--